Docosahexaenoic acid (DHA): An essential nutrient and a nutraceutical for brain health and diseases. (September 2018) - Sun, Grace Y.; Simonyi, Agnes; Fritsche, Kevin L.; Chuang, Dennis Y.; Hannink, Mark; Gu, Zezong; Greenlief, C. Michael; Yao, Jeffrey K.; Lee, James C.; Beversdorf, David Q.
Abstract: Docosahexaenoic acid (DHA), a polyunsaturated fatty acid (PUFA) enriched in phospholipids in the brain and retina, is known to play multi-functional roles in brain health and diseases. While arachidonic acid (AA) is released from membrane phospholipids by cytosolic phospholipase A2 (cPLA2 ), DHA is linked to action of the Ca 2+ -independent iPLA2. DHA undergoes enzymatic conversion by 15-lipoxygenase (Alox 15) to form oxylipins including resolvins and neuroprotectins, which are powerful lipid mediators. DHA can also undergo non-enzymatic conversion by reacting with oxygen free radicals (ROS), which cause the production of 4-hydoxyhexenal (4-HHE), an aldehyde derivative which can form adducts with DNA, proteins and lipids. In studies with both animal models and humans, there is evidence that inadequate intake of maternal n-3 PUFA may lead to aberrant development and function of the central nervous system (CNS). What is less certain is whether consumption of n-3 PUFA is important in maintaining brain health throughout one's life span. Evidence mostly from non-human studies suggests that DHA intake above normal nutritional requirements might modify the risk/course of a number of diseases of the brain. This concept has fueled much of the present interest in DHA research, in particular, in attempts to delineate mechanisms whereby DHA may serve as a nutraceutical and confer neuroprotective effects. Current studies have revealed ability for the oxylipins to regulation of cell redox homeostasis through the Nuclear factor (erythroid-derived 2)-like 2/Antioxidant response element (Nrf2/ARE) anti-oxidant pathway, and impact signaling pathways associated with neurotransmitters, and modulation of neuronal functions involving brain-derived neurotropic factor (BDNF). This review is aimed at describing recent studies elaborating these mechanisms with special regard to aging and Alzheimer's disease, autism spectrum disorder, schizophrenia, traumatic brain injury, and stroke. Highlights: Multi-function roles of DHA in maintaining brain health throughout the life span. DHA undergoes enzymatic and non-enzymatic conversions to form oxilipins. 4-Hydroxyhexenal (4-HHE) regulates cell redox homeostasis through Nrf2/ARE. DHA derived lipid mediators are neuroprotective and ameliorate neurological disorders.